What should be the purpose of a law defending free competition?: Regarding what is established in the Organic Law of Regulation and Control of Market Power of Ecuador - Gómez-Apac, Hugo (DICERE Revista de Derecho y Estudios Internacionales, 2024)
This paper takes a position on what the purpose of a competition law should be, which is to protect the competitive process (and not the competitors) because it generates economic efficiencies in the market that improve consumer welfare. Likewise, the objective of Ecuador’s competition law is analyzed, which, after being modified in 2023, establishes that its purpose is the protection of the general welfare through economic efficiency.